2021
DOI: 10.1161/jaha.121.021002
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Activation Disorder and Postural Orthostatic Tachycardia Syndrome: A Clinical Association

Abstract: Background Recently there has been increased interest in a possible association between mast cell activation (MCA) disorder and postural orthostatic tachycardia syndrome (POTS). This study examined the frequency with which symptoms and laboratory findings suggesting MCA disorder occurred in patients diagnosed with POTS. Methods and Results Data were obtained from patients in whom symptoms and orthostatic testing were consistent with a POTS diagnosis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…One of the possible mechanisms underlying POTS is activation of basophils and mast cells by parasympathetic neurons. This hypothesis is supported by a recent study where two thirds of individuals with POTS demonstrated increased histamine or other mast cell mediators in the blood in the setting of postural tachycardia (15). The present study will investigate whether this also occurs in post COVID-19 POTS.…”
Section: Evidence For Lhc/pots and Immunologic Dysregulationsupporting
confidence: 54%
“…One of the possible mechanisms underlying POTS is activation of basophils and mast cells by parasympathetic neurons. This hypothesis is supported by a recent study where two thirds of individuals with POTS demonstrated increased histamine or other mast cell mediators in the blood in the setting of postural tachycardia (15). The present study will investigate whether this also occurs in post COVID-19 POTS.…”
Section: Evidence For Lhc/pots and Immunologic Dysregulationsupporting
confidence: 54%
“…In mast cell activation disorder, the inappropriate release of histamine and other mast cell mediators in response to physical activity or orthostatic stress may lead to orthostatic tachycardia [49]. Flushing, headaches, and gastrointestinal symptoms are more prevalent in these individuals, and a recent study showed markedly elevated prostaglandins and histamine markers in patients with gastrointestinal complaints, reinforcing the case for a mast cell activation disorder in a subset of POTS patients [78]. A case of mast cell activation syndrome was described in a 50-year-old female with previous COVID-19 with signs and symptoms of POTS [52].…”
Section: How Does Sars-cov-2 Infection Cause Long-term Dysautonomia?mentioning
confidence: 97%
“… 16 Furthermore, mast cell activation disorder (MCAD), a condition in which mast cells increase in number or excessively release inflammatory mediators, 31 was considered to be a comorbidity of adult POTS, and some of which might be secondary to allergic disorders. 32 , 33 A previous study on adults reported that patients with POTS were complicated with abnormal mast cell activation and significant increases in methylhistamine, leukotriene, and prostaglandin D 2 in their urine. 34 These inflammatory vasoactive substances may aggravate the dilation of peripheral blood vessels and increase vasopermeability, which can theoretically facilitate the occurrence of OI.…”
Section: Discussionmentioning
confidence: 99%